Soluble Adhesion Molecules and Endothelial Cell Damage in HIV Infected Patients - Seigneur, Martine; Constans, Joël; Blann, Andrew; Renard, Martine; Pellegrin, Jean Luc; Amiral, Jean; Boisseau, Michel; Conri, Claude (Thrombosis and Haemostasis, 1997)
Endothelial damage is present in HIV infection but our understanding of markers and mechanisms is incomplete. We found increased levels of markers of endothelial cell damage such as von Willebrand factor (vWf), soluble thrombomodulin (sTM) and adhesion molecule E- selectin in 90 subjects seropositive for HIV relative to healthy controls. sTM was strongly raised in those patients with the lowest CD4+ cell count (p <0.001), but levels of vWf increased at each incremental fall in CD4+ cell count and the two indices correlated significantly (r = -0.485, p <0.001). vWf correlated strongly with levels of the inflammatory cytokines tumor necrosis factor (TNF-α) and alpha interferon (IFN-α) but sTM correlated only weakly with IFN-α. We suggest that increased vWf is largely the result of inflammatory stimulus of the endothelium but that sTM is found only in those patients with more severe disease, and so truely represents endothelial damage.